Experimental investigation of the thermal and mechanical stability of rocks for high-temperature thermal-energy storage. (1st October 2017) - Becattini, Viola; Motmans, Thomas; Zappone, Alba; Madonna, Claudio; Haselbacher, Andreas; Steinfeld, Aldo
Highlights: Six Alpine rocks were investigated for high-temperature thermal-energy storage. The rocks were cycled between 100 and 600 °C with a heating rate of 2.6 °C/min. Cycling decreases the specific heat capacity and increases the porosity. The changes induced by cycling are attributed to physical and chemical reactions. Rocks suitable for high-temperature thermal-energy storage were identified. Abstract: Six types of rocks of Alpine origin were investigated for their suitability for high-temperature packed-bed thermal-energy storage. The rocks were thermally cycled in laboratory furnaces between about 100 °C and 600 ° C with a heating rate of 2.6 ° C /min and assessed in terms of their specific heat capacity and porosity as well as the degree of cracking, fracturing, and disintegration. Thermal cycling was found to lead to decreases in the specific heat capacity and increases in the porosity of the rocks. These changes are explained by physical and chemical reactions such as mineral dehydration, deserpentinization, decarbonation, and the quartz-inversion reaction. Simulations of a 23 MWh industrial-scale thermal-energy storage show that the decrease in the specific heat capacity does not have a significant impact on the effective storage capacity, utilization factor, and exergy efficiency. To avoid fracturing of rocks, foliated rocks and rocks rich in calcite and/or quartz, such as limestones and sandstones, are found to be unsuitable when exposed to temperatures higher than about 600 ° C or 573 ° C, respectively. Mafic rocks, felsic rocks, serpentinite, and quartz-rich conglomerates are judged to be suitable for high-temperature thermal-energy storage.